PENDEKATAN DALAM PENGELOLAAN KELAS - NENENG NURMALASARI (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2019)
Abstract : Education centered on the learning process in the classroom. The success in achieving educational goals depends on classroom management conducted by the teacher. Classroom management is an activity carried out by teachers to create a conducive learning environment, so that learning objectives can be achieved properly. Class is inhabited by a variety of different characters from each student, which can lead to various types of conflicts that could interfere with learning activities. In this case, a teacher must be able to control class conditions with various approaches, including authoritarian approaches, intimidation approach, permissive approach, recipe approach, behaviour change approach, socio-emotional approach, group approach, and electrical or pluralistic approach, in order to allow the learning process carried out as expected, therefore learning objectives could be achieved. Keywords : Education, learning, and Classroom Management